Next Generation Sequencing: Potential and Application in Drug Discovery - Navneet Kumar Yadav; Pooja Shukla; Ankur Omer; Shruti Pareek; R. K. Singh (The Scientific World Journal)
The world has now entered into a new era of genomics because of the continued advancements in the next generation high throughput sequencing technologies, which includes sequencing by synthesis-fluorescent in situ sequencing (FISSEQ), pyrosequencing, sequencing by ligation using polony amplification, supported oligonucleotide detection (SOLiD), sequencing by hybridization along with sequencing by ligation, and nanopore technology. Great impacts of these methods can be seen for solving the genome related problems of plant and animal kingdom that will open the door of a new era of genomics. This may ultimately overcome the Sanger sequencing that ruled for 30 years. NGS is expected to advance and make the drug discovery process more rapid.